Die Käfer der Paläarktis: Probleme und Perspektiven. - Löbl, Ivan (Contributions to Entomology = Beiträge zur Entomologie, 2006)
Taxonomy provides basic information about the diversity of life, and a universal language that unambiguously vehicles such information. Nevertheless, a demise of taxonomy is widespread in many European countries and results in a bio-information crisis. Based on experience with Palaearctic Coleoptera and a large number of coleopterists, the taxonomic impediment is seen as a consequence of a number of factors. Among them, the underestimation of the variability of species, the believe in new technologies that are assumed to provide more relevant data than complex knowledge, the inadequate means of evaluation of work in taxonomy, the confusion of taxonomy with its means of identification, and the expectation of finality in taxonomic research appear to have a particularly negative impact. New methods proposed as salvage for taxonomy are discussed. They appear either ill-based, or may punctually approve deficits, but luck potential to reverse the present situation. It is suggested that true progress requires adequate support, and a priori free re-evaluation of taxonomy (and biosystematics) in universities as in museums. Should the present tendencies in many European countries last, the professional taxonomy and associated knowledge will have to be imported, or may vanish.KeywordsBio-information crisis, taxonomy, impediments, perspectives.